TEACHER SCAFFOLDING PRACTICES IN PLAYING L-STEAM IN EARLY CHILDHOOD - Fatimatuzahroh; Yuliani Nurani; R Sri Martini Meilanie (RADJA PUBLIKA, 2026)
L-STEAM play in early childhood education positions teachers as facilitators who play a crucial role in providing learning support through responsive interactions. However, studies on teacher scaffolding practices in the context of L-STEAM play are still relatively limited, particularly in learning situations that take place in early childhood education (PAUD) units. This study aims to explore teacher scaffolding practices in L-STEAM play in early childhood. The study used a qualitative approach with a case study design at ADC+ Kindergarten. The study participants consisted of five kindergarten group teachers and one principal, while eight children aged 5–6 years were involved as observation subjects. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results showed that teacher scaffolding practices were realized through questioning, prompting, modeling, feedback, and reinforcement provided gradually according to the children's needs during L-STEAM play. These forms of scaffolding encouraged children to be more active in exploring, expressing ideas, trying various alternatives, and communicating their learning experiences. The research findings confirm that scaffolding practices are an important part of teachers' pedagogical practices that support the creation of meaningful and child-centered L-STEAM play experiences.